2019
DOI: 10.1017/s0007114518003811
|View full text |Cite
|
Sign up to set email alerts
|

Total polyphenol intake and breast cancer risk in the Seguimiento Universidad de Navarra (SUN) cohort

Abstract: Polyphenols are a wide family of phytochemicals present in diverse foods. They might play a role in cancer development and progression. In vivo and in vitro studies have suggested beneficial properties and potential mechanisms. We aimed to evaluate the association between total and main classes of polyphenol intake and breast cancer (BC) risk in the Seguimiento Universidad de Navarra project – a prospective Mediterranean cohort study. We included 10 713 middle-aged, Spanish female university graduates. Polyphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 32 publications
0
9
1
1
Order By: Relevance
“…In contrast, there is controversy about our results with other published studies as Feng et al [36] and Gardeazabal [37]. The first one determined that the consumption of flavonoids was associated with lower BC risk [36].…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…In contrast, there is controversy about our results with other published studies as Feng et al [36] and Gardeazabal [37]. The first one determined that the consumption of flavonoids was associated with lower BC risk [36].…”
Section: Discussioncontrasting
confidence: 60%
“…The first one determined that the consumption of flavonoids was associated with lower BC risk [36]. The second one (that studied the total intake of different classes of polyphenols) did not find any significant associations between BC risk and the intake of total flavonoids, total lignans, stilbenes and total phenolic acids [37], although achieving a nonsignificant risk reduction. However, a Fink et al [38] study found a significant inverse association for lignans but not for total flavonoid consumption.…”
Section: Discussionmentioning
confidence: 99%
“…However, in postmenopausal women, they observed an inverse association between breast cancer risk and total polyphenol intake (HR: 0.31, 95% CI: 0.13–0.77) [97]. Because they have antioxidant activity and similar chemical compositions as oestrogens, flavonoids are able to reduce menopause symptoms [98]. However, further research is needed to demonstrate the effect of flavonoid intake on pre- and post-menopause breast cancer risk.…”
Section: Antioxidant Activity Of Dietary Flavonoids and Cancer Incmentioning
confidence: 99%
“…In addition, several studies have reported that a high adherence to MD is associated with a lower risk of the incidence of BC in post-menopausal women (41). A prospective cohort study conducted in the Mediterranean included 10,713 middle-aged, Spanish female university graduates and revealed an inverse association between the total polyphenol intake and the risk of BC for post-menopausal women (42).…”
Section: Breast Cancermentioning
confidence: 99%